Teacher Education and the “Good Teacher” - Worrell, Patricia (Daily Express, 2004)
This article identifies possible issues to be addressed by participants at a Symposium on Teacher Education, which was scheduled to begin at The University of the West Indies (UWI) on 28 April, 2004. It suggests that one important topic that was likely to be the subject of deliberation at the Symposium was the definition of a "good teacher," and identifies some of the dimensions of "goodness" that might be considered as (a) the ethical and moral dimensions, (b) effectiveness, and (c) empowerment
Keywords: Teacher characteristics; Teacher effectiveness; Teacher education curriculum; Trinidad and Tobago